2012
DOI: 10.1074/jbc.m111.298414
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Clostridium difficile Toxin A Glucosyltransferase Activity

Abstract: Background: C. difficile TcdA and TcdB glucosylate small GTPases. Results: Structural and functional studies reveal comparable activities with Rho substrates, enhanced activities following autoprocessing, and TcdA-specific modification of Rap2A. Conclusion: TcdA is a potent enzyme and modifies a broader array of GTPase substrates than TcdB. Significance: These findings highlight the importance of autoprocessing for activity and reveal differences in target specificity between the toxins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
102
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(112 citation statements)
references
References 51 publications
10
102
0
Order By: Relevance
“…However, it is still possible that Y219 in NleB1 interacts with UDP-GlcNAc by hydrophobic stacking, as observed for numerous aromatic side chain-containing amino acids (39,54,55). Alternatively, Y219 in NleB1 may interact with UDP-GlcNAc via hydrogen bonding, as the equivalent tyrosine in C. difficile toxin A (Y283) is positioned in close proximity to two carbonyls of the ribose ring and a water molecule (56,57 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is still possible that Y219 in NleB1 interacts with UDP-GlcNAc by hydrophobic stacking, as observed for numerous aromatic side chain-containing amino acids (39,54,55). Alternatively, Y219 in NleB1 may interact with UDP-GlcNAc via hydrogen bonding, as the equivalent tyrosine in C. difficile toxin A (Y283) is positioned in close proximity to two carbonyls of the ribose ring and a water molecule (56,57 …”
Section: Discussionmentioning
confidence: 99%
“…Like many other A-B toxins that mediate their own delivery into cells, high-resolution structures of the enzymic A domains (11)(12)(13) and the receptor-binding portion of the B domains of glucosylating toxin family members are known (14,15), whereas the structure and mechanism of the pore-forming translocation domain remains poorly characterized. These interconnected processes have been proposed to be mediated by the central ∼1,000-aa D domain (i.e., amino acids 801-1,850); however, with the absence of any structural information for this domain in either the prepore or pore state, no framework exists for resolving the functional determinants for this large domain that govern pore formation and translocation.…”
mentioning
confidence: 99%
“…Until recently, the structural reasons for this difference in substrate targeting were not known. A study by Pruitt and colleagues found that the overall structure of the glucosyltransferase domain (GTD) in TcdA is similar to that in TcdB; however, the GTD of TcdA has a larger net negative charge of surface-exposed residues than that in TcdB (137). Moreover, the UDP-glucosebinding pocket of TcdA is positively charged, but the corresponding region in TcdB exhibits a large net negative charge.…”
Section: Mechanism Of Action Of Tcda and Tcdbmentioning
confidence: 99%